Seafire - Parker, Natalie C. (2018)
After her family is killed by corrupt warlord Aric Athair and his bloodthirsty army of Bullets, Caledonia Styx is left to chart her own course on the dangerous and deadly seas. She captains her ship, the Mors Navis, with a crew of girls and women just like her, whose lives have been turned upside down by Aric and his men. The crew has one misson: stay alive, and take down Aric's armed and armored fleet. But when Caledonia's best friend and second-in-command just barely survives an attack thanks to help from a Bullet looking to defect, Caledonia finds herself questioning whether or not to let him join their crew. Is this boy the key to taking down Aric Athair once and for all or will he threaten everything the women of the Mors Navis have worked for?
Keywords: Ship captains -- Fiction; Sex role -- Fiction; Seafaring life -- Fiction; Ship captains -- Juvenile fiction; Sex role -- Juvenile fiction; Seafaring life -- Juvenile fiction; Young adult fiction; Action and adventure fiction